Dietary Correlates of Oral and Gut Microbiota in the Water Monitor Lizard, Varanus salvator (Laurenti, 1768) - Du, Yu; Chen, Jun-Qiong; Liu, Qian; Fu, Jian-Chao; Lin, Chi-Xian; Lin, Long-Hui; Li, Hong; Qu, Yan-Fu; Ji, Xiang (Frontiers in Microbiology, 2022)
Numerous studies have demonstrated that food shapes the structure and composition of the host's oral and gut microbiota. The disorder of oral and gut microbiota may trigger various host diseases. Here, we collected oral and gut samples from wild water monitor lizards (Varanus salvator) and their captive conspecifics fed with bullfrogs, eggs and depilated chicken, aiming to examine dietary correlates of oral and gut microbiota. We used the 16S rRNA gene sequencing technology to analyze the composition of the microbiota. Proteobacteria and Bacteroidota were the dominant phyla in the oral microbiota, and so were in the gut microbiota. The alpha diversity of microbiota was significantly higher in the gut than in the oral cavity, and was higher in captive lizards than in wild conspecifics. Comparing the relative abundance of oral and gut bacteria and their gene functions, differences among different animal groups presumably resulted from human contact in artificial breeding environments and complex food processing. Differences in gene function might be related to the absolute number and/or the taxonomic abundance of oral and gut microorganisms in the wild and the water environment. This study provides not only basic information about the oral and gut microbiota of captive and wild water monitor lizards, but also an inference that feeding on frogs and aquatic products and reducing human exposure help water monitor lizards maintain a microbiota similar to that in the wild environment.